Faktor-Faktor Yang Mempengaruhi Hasil Belajar Ips Siswa Madrasah Ibtidaiyah Kelas V Di Kabupaten Bantul Yogyakarta. - Sukati . (Universitas Alma Ata, 2013)
This study aims to investigate the effects of the attention of students’ parents (X1), teachers’ teaching competence (X2), students’ learning motivation (X3), and learning facilities (X4), as individual variables and as an aggregate, on the learning achievement of Social Studies (SS) the students of Madrasah Ibtidaiyah (MI) in di Bantul Regency Yogyakarta.This was an ex post facto study with a population comprising 194 students of MI fifth grade in Bantul Regency Yogyakarta. The sample consisted of 137 students with cluster sampling technique.The data were collected through questionnaires, i.e. questionnaire 1 to collect the data on the variable of the attention of students’ parents, questionnaire 2 to collect the data on the variable of teachers’ teaching competence, questionnaire 3 to collect the data on the variable of students’ learning motivation, and questionnaire 4 to collect the data on the variable of learning facilities. The study was conducted from November to December 2012. The data were analyzed using the simple linear regression and the multiple linear regression.The results of the study are as follows shows that: 1) there is a significant effect of the attention of students’ parents on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta with the significance level as much as 0.012 < 0.05; 2) there is a significant effect of teachers’ teaching competence on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta with the significance level as much as 0.003 < 0.05; 3) there is a significant effect of students’ learning motivation on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta with the significance level as much as 0.007 < 0.05; 4) there is a significant effect of learning facilities on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta with the significance level as much as 0.008 < 0.05; and 5) there are effects of the attention of students’ parents, teachers’ teaching competence, students’ learning motivation, and learning facilities as an aggregate on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta as much as 57.4% with Fobserved = 44.76 > Ftable = 8,229 and p = 0.000 < 0.05. The results show that the factors of the attention of students’ parents, teachers’ teaching competence, students’ learning motivation, and learning facilities can have effects on the learning achievement of SS the students of MI fifth grade in Bantul Regency Yogyakarta . Keyword: learning achievement